2012
DOI: 10.1088/0004-637x/753/1/88
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between the Coronal Mass Ejection Acceleration and the Non-Thermal Flare Characteristics

Abstract: We investigate the relationship between the main acceleration phase of coronal mass ejections (CMEs) and the particle acceleration in the associated flares as evidenced in Reuven Ramaty High Energy Solar Spectroscopic Imager non-thermal X-rays for a set of 37 impulsive flare-CME events. Both the CME peak velocity and peak acceleration yield distinct correlations with various parameters characterizing the flare-accelerated electron spectra. The highest correlation coefficient is obtained for the relation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 44 publications
6
32
0
Order By: Relevance
“…Thus the distribution is slightly asymmetric with a few more events where CME acceleration appears to rise earlier than the rise of flare reconnection. This asymmetry is consistent with but less remarkable than that using the CME acceleration and the hard X-ray emission reported by Berkebile-Stoiser et al (2012). Fig.…”
Section: Start Times Of Cme Acceleration and Flare Reconnectionsupporting
confidence: 87%
“…Thus the distribution is slightly asymmetric with a few more events where CME acceleration appears to rise earlier than the rise of flare reconnection. This asymmetry is consistent with but less remarkable than that using the CME acceleration and the hard X-ray emission reported by Berkebile-Stoiser et al (2012). Fig.…”
Section: Start Times Of Cme Acceleration and Flare Reconnectionsupporting
confidence: 87%
“…In this respect it should be stressed that detailed inspection of graphs presented in these two studies again discloses that the acceleration starts before the flare impulsive phase, represented now directly by the HXR burst, and ends after it. Finally, Berkebile-Stoiser et al (2012) showed that the hardness of the flare HXR spectra is distinctly correlated with the CME acceleration. In most of the events, the CME acceleration started before the flare.…”
Section: Observational Aspectsmentioning
confidence: 95%
“…However, it has been shown that the acceleration profile of CMEs tends to peak during this period, too (cf. Zhang et al, 2001;Maričić et al, 2007;Temmer et al, 2008;Berkebile-Stoiser et al, 2012). Since coronal waves are highly associated with CMEs too (Section 5.2), timing alone cannot be used to make a distinction between a flare-related and a CME-related wave launch mechanism.…”
Section: Solar Flaresmentioning
confidence: 99%